Contribution of the Sn 5s state to the SnS valence band: direct observation via ARPES measurements. (1st June 2022) - Suzuki, Issei; Kawanishi, Sakiko; Tanaka, Kiyohisa; Omata, Takahisa; Tanaka, Shin-ichiro
Abstract: Tin sulfide (SnS) is a compound semiconductor that has been studied for a wide range of applications, including solar cells and thermoelectric materials. In this study, the electronic structure of the SnS valence band, which is important for such applications, was investigated via angle-resolved photoelectron spectroscopy with two different excitation energies in the extreme ultraviolet region (21 and 60 eV). The contribution of the Sn 5s state to the SnS valence band was determined in relation to the k -vector by utilizing the fact that the cross section of Sn 5s state varies significantly compared to those of other states in the extreme ultraviolet region. The experimental results demonstrate that the Sn 5s state significantly contributed to the k -vector around the valence band maximum (VBM) and second VBM (VBM1).